Biophysical characterisation of human eukaryotic elongation factor 1 Beta and its interaction with human eukaryotic elongation factor 1 Gamma - Elebo, Nnenna Chioma (My University, 2017)
Eukaryotic protein synthesis occurs in three phases: initiation, elongation and termination. The elongation phase is mediated by elongation factors. Elongation factors are divided into elongation factor 1 (eEF1) and elongation factor 2 (eEF2). Elongation factor 1 complex are proteins that mediates the extension of growing polypeptide chains by adding one amino acid residue at a time. The eEF-1 complex comprises of four subunits, eEF1α, eEF1β, eEF1γ and eEF1δ. The β-subunit of elongation factor 1 complex (eEF1) plays a central role in the elongation step of eukaryotic protein biosynthesis, which essentially involves interaction with the α-subunits (eEF1α) and γ-subunits (eEF1γ). To biophysically characterise heEF1β, three E. coli expression vector systems was constructed for recombinant expression of the full length (FL-heEF1β), amino terminus (NT-heEF1β) and the carboxyl terminus (CT-heEF1β) regions of the protein. NT-heEF1β was created from the FL-heEF1β by site-directed mutagenesis using mutagenic forward and reverse primers. The results suggest that heEF1β is predominantly alpha-helical and possesses an accessible hydrophobic cavity in the CT-heEF1β. Both FL-heEF1β and NT-heEF1β forms dimers of size 62 kDa and 30 kDa, respectively, but the CT-heEF1β is monomeric. FL-heEF1β interacts with the N-terminus GST-like domain of heEF1γ (NT-heEF1γ) to form a 195 kDa complex, or a 230 kDa complex in the presence of oxidised glutathione. On the other hand, NT-heEF1β forms a 170 kDa complex with NT-heEF1γ and a high molecular weight aggregate of size greater than 670 kDa. This study affirms that the interaction between heEF1β and heEF1γ subunits occurs at the N-terminus regions of both proteins, also the N-terminus region of heEF1β is responsible for its dimerisation and the C-terminus region of heEF1β controls the formation of an ordered eEF1β-γ oligomer, a structure that may be essential in the elongation step of eukaryotic protein biosynthesis.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. July, 2017
Keywords: Proteins--Synthesis; Eukaryotic cells